Impact of general manager characteristics on the export performance of manufacturing companies in Turkey - Öz, Özge. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2010., 2010)
The objective of this study is to investigate the relation between export performance of manufacturing firms and the characteristics of their general managers. A survey of the literature revealed several general manager characteristics that have the potential to influence export performance. Some of these parameters are age, educational background, linguistic skills, technical capabilities, risk tolerance, and foreign country exposure. In this study, age, educational attainment, and foreign country exposure were chosen as general manager characteristics to be investigated. General managers constituting the sample were randomly selected among manufacturing companies quoted on Istanbul Stock Exchange (ISE).The data were collected mainly from archival resources such as company yearbooks, annual reports, corporate governance compliance reports of the firms in the sample. Frequency analysis and non-parametric Mann Whitney U tests were run for the statistical analysis of the data set. Results of the study reveal no direct relationship discovered between objective general manager characteristics and export performance of firms in Turkey.
Keywords: Business -- Research -- Turkey.; International business enterprises -- Management.